Historical and Philosophical Analysis of Free Will as the Genesis of Understanding Law - Savchenko, Viktor (Teisė, 2023)
The article considers the views of prominent scientists on the legal nature of free will. The article proves that historically, the primary purpose of the law was to regulate social relations and free will. The Author studied the evolution of views on free will in direction through Antiquity, the Middle Ages, the Reformation and modern understanding.